Uji Efektivitas Antibiotik Ekstrak Daun Belimbing Wuluh (Averrhoa Billimbi L) Terhadap Pertumbuhan Staphyloccus aureus Secara In Vitro - Dhifo Indratama; Yenita Yenita (JURNAL PANDU HUSADA, 2020)
Abstract: Infection is the most common disease in Indonesia. Infection diseases arecaused by microorganisms such as the Staphylococcus aureus. While in fact, many plantscan be used as traditional medicine, one of those is the leaves of belimbing wuluh tree (Averrhoa bilimbi L.) This study aims to determine the inhibitory power of leaves ofCucumber tree (Averrhoa bilimbi L.) on growth of Staphylococcus aureus in vitro. Thisstudy used an experimental method. The technique used to measure antibiotic activity isthe method of disk diffusion and continued by Kruskal- Wallis test and Mann-Whitney test.Leaves of belimbing wuluh tree (Averrhoa bilimbi L.) at concentrations of 40%, 60%,80%, 100%, amoksisilin, and aquabidest resulted in average diameter of clear zone.leaves of belimbing wuluh tree (Averrhoa bilimbi L.) have an inhibitory power againstStaphylococcus aureus. Keywords: Leaves of belimbing wuluh tree (Averrhoa bilimbi L.), Staphylococcusaureus.